Emerging issues and current trends in assistive technology use 2007-1010: practising, assisting and enabling learning for all - Abbott, Chris; Brown, David; Evett, Lindsay; Standen, Penny (Informa Healthcare, 2014)
Following an earlier review in 2007, a further review of the academic literature relating to the uses of assistive technology (AT) by children and young people was completed, covering the period 2007-2011. As in the earlier review, a tripartite taxonomy: technology uses to train or practise, technology uses to assist learning and technology uses to enable learning, was used in order to structure the findings. The key markers for research in this field and during these three years were user involvement, AT on mobile mainstream devices, the visibility of AT, technology for interaction and collaboration, new and developing interfaces and inclusive design principles. The paper concludes by locating these developments within the broader framework of the Digital Divide.